Impaired antigen-specific B-cell responses after Influenza vaccination in kidney transplant recipients receiving co-stimulation blockade with Belatacept - Pernin, Vincent; Meneghini, Maria; Torija, Alba; Jouve, Thomas; Del Bello, Arnaud; Sanz-Muñoz, Iván; Eiros, Jose Maria; Donadeu, Laura; Polo, Carol; Morandeira, Francisco; Navarro, Sergio; Masuet, Cristina; et al. (Frontiers in Immunology, 2022)
Emerging data suggest that costimulation blockade with belatacept effectively controls humoral alloimmune responses. However, whether this effect may be deleterious for protective anti-infectious immunity remains poorly understood. We performed a mechanistic exploratory study in 23 kidney transplant recipients receiving either the calcineurin-inhibitor tacrolimus (Tac, n=14) or belatacept (n=9) evaluating different cellular immune responses after influenza vaccination such as activated T follicular Helper (Tfh), plasmablasts and H1N1 hemagglutinin (HA)-specific memory B cells (HA+mBC) by flow-cytometry, and anti-influenza antibodies by hemagglutination inhibition test (HI), at baseline and days 10, 30 and 90 post-vaccination. The proportion of CD4+CD54RA-CXCR5+ Tfh was lower in belatacept than Tac patients at baseline (1.86%[1.25-3.03] vs 4.88%[2.40-8.27], p=0.01) and remained stable post-vaccination. At M3, HA+mBc were significantly higher in Tac-treated patients (0.56%[0.32-1.49] vs 0.27%[0.13-0.44], p=0.04) and correlated with activated Tfh numbers. When stratifying patients according to baseline HA+mBc frequencies, belatacept patients with low HA+mBC displayed significantly lower HA+mBc increases after vaccination than Tac patients (1.28[0.94-2.4] vs 2.54[1.73-5.70], p=0.04). Also, belatacept patients displayed significantly lower seroprotection rates against H1N1 at baseline than Tac-treated patients (44.4% vs 84.6%) as well as lower seroconversion rates at days 10, 30 and 90 after vaccination (50% vs 0%, 63.6% vs 0%, and 63.6% vs 0%, respectively). We show the efficacy of belatacept inhibiting T-dependent antigen-specific humoral immune responses, active immunization should be highly encouraged before starting belatacept therapy.